Work-related stress assessment among a garment factory employees in Bangalore suburban locality - Anandi, Basavakumar S.; Rajaram, Dinesh; B. A., Aravind; Sukumar, Gautham M.; K., Radhika (International Journal Of Community Medicine And Public Health, 2017)
Background: India’s Garment Industry has been rapidly growing in last few years. The Garment Industry is of major importance to the Indian economy as it contributes substantially to India’s export earnings. Thus employees working in the above sociological context of working life are expected to be affected by the general acceleration of the pace of life, contributing to work intensification and constant time pressure. Managers play a key role in reducing the significant sources of stress and shaping the future of employees. Thus the above study was undertaken among managers and supervisory level staff. The objectives of the study were to estimate the magnitude and level of work-related stress and to find the association of socio-demographic factors with work-related stress in garment manufacturing factory. Methods: A cross-sectional study was undertaken for 4 months, from October 2015 to January 2016, in a selected garment factory, located in the periphery of Bangalore city. A total of 167 supervisors and 41 managers, were included in the study. Stress was assessed by using ‘Tool to assess and classify work stress and associated symptoms’, developed by Centre for public health, NIMHANS. Results: Prevalence of work-related stress was 26% (95% CI; 18.04-26.36). Managers had higher prevalence of stress (29.3%) when compared to supervisors (25.1%). Majority of managers were perceived to have moderate stress level (58.4%) when compared to supervisors (26.10%). Among all the socio-demographic factors; age, total monthly income, travel time and mode of transport were significantly associated with work-related stress (p<0.05). Conclusions: Organization changes viz., effort-reward imbalances, needs to be corrected and appropriate transport facilities meeting the employee requirements have to be provided, to cope up stress associated with travelling.